Physical-chemical treatment of water and wastewater - Sincero, Arcadio P., ....-; Sincero, Gregoria A., ....- (Boca Raton : CRC, 2003)
Samenvatting:The books currently available on this subject contain some elements ofphysical-chemical treatment of water and wastewater but fall short ofgiving comprehensive and authoritative coverage. They contain someequations that are not substantiated, offering empirical data based onassumptions that are therefore difficult to comprehend. This text bringstogether the information previously scattered in several books and addsthe knowledge from the author's lectures on wastewaterengineering.Physical-Chemical Treatment of Water and Wastewater is notonly descriptive but is also analytical in nature. The work covers thephysical unit operations and unit processes utilized in the treatment ofwater and wastewater. Its organization is designed to match the majorprocesses and its approach is mathematical. The authors stress thedescription and derivation of processes and process parameters inmathematical terms, which can then be generalized into diverse empiricalsituations. Each chapter includes design equations, definitions ofsymbols, a glossary of terms, and worked examples. One author is anenvironmental engineer and a professor for over 12 years and the otherhas been in the practice of environmental engineering for more than 20years. They offer a sound analytical mathematical foundation anddescription of processes. Physical-Chemical Treatment of Water andWastewater fills a niche as the only dedicated textbook in the area ofphysical and chemical methods, providing an analytical approachapplicable to a range of empirical situations
Keywords: Afvalwaterzuivering; Drinkwaterzuivering